2014
DOI: 10.1097/mjt.0b013e318274db78
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Analgesic Efficacy of Dexketoprofen Trometamol and Meperidine HCl in the Relief of Renal Colic

Abstract: In this study, the analgesic effects of dexketoprofen trometamol and meperidine hydrochloride were compared in patients diagnosed with renal colic. This study was a prospective, randomized, double-blind study. Fifty-two patients, between the ages of 18 and 70 years who were diagnosed with renal colic, were enrolled in the study after obtaining ethics committee approval. Before drug injection, dexketoprofen trometamol and meperidine hydrochloride were placed in closed envelopes, and the patients were randomly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
11
0
2
Order By: Relevance
“…More specifically, the efficacy and safety among NSAIDs, opioids, paracetamol, combination therapy, and placebo were compared according to the classification and pharmacological mechanism of these five interventions in the first stage. Our analysis confirmed that NSAIDs are superior to opioids and paracetamol, which is consistent with some previous studies (Cordell et al, 1996; Wood et al, 2000; Ay et al, 2014; Kaynar et al, 2015; Pathan et al, 2016). The European Association of Urology (EAU) guideline for urolithiasis in 2018 (EAU Guidelines Office) also recommended NSAIDs for very effective treatment of acute renal colic and found they were superior to opioids.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, the efficacy and safety among NSAIDs, opioids, paracetamol, combination therapy, and placebo were compared according to the classification and pharmacological mechanism of these five interventions in the first stage. Our analysis confirmed that NSAIDs are superior to opioids and paracetamol, which is consistent with some previous studies (Cordell et al, 1996; Wood et al, 2000; Ay et al, 2014; Kaynar et al, 2015; Pathan et al, 2016). The European Association of Urology (EAU) guideline for urolithiasis in 2018 (EAU Guidelines Office) also recommended NSAIDs for very effective treatment of acute renal colic and found they were superior to opioids.…”
Section: Discussionsupporting
confidence: 93%
“…There are also differences that have been reported in terms of need for additional analgesic and adverse effects based on administration methods. Compared to opioids, NSAIDs have been demonstrated to have less need for additional analgesic when administered intravenously and less rates of vomiting when administered only intramuscularly [22][23][24] . On the other hand, despite the existing complications described for ESP block in the literature, there were not any complications or adverse effects during the course of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the case presented here is the first instance in the literature of AS after the use of DT intravenously. Parenteral DT is widely used in acute pain management in the EDs 2, 3, 4. Parenterally or orally administered DT has a good tolerability profile and high analgesic potency 1, 8, 9.…”
Section: Discussionmentioning
confidence: 99%
“…Oral DT was approved in the European countries through a Mutual Recognition Procedure in 1998 and parenteral formulation in 2002 1 . Parenteral DT is widely used in acute pain management in the emergency department (ED) settings 2, 3, 4. Although diarrhea, indigestion, nausea, stomach pain, and vomiting are described as common adverse drug reactions in the product information of DT, anaphylactic shock (AS) secondary to use of DT is very rare with an incidence of <0.01% 5 .…”
Section: Introductionmentioning
confidence: 99%